Comparison of Proctor and Uniaxial Compression Tests for Selected Soils (Agricultural Engineering, 2018)
The objective of this paper was to compare the results of soil material compaction carried out with the use of the Proctor and uniaxial compression tests in order to find relations between these methods. Soil material in the form of loose mass was collected from the layer deposited at the depth from 35 to 60 cm in order to determine its typical properties (textural group, density of solid particles, humus content, reaction, plastic and liquid limits) and in order to compact it in the Proctor apparatus and in the uniaxial compression test. Results of both tests were used for construction of regression models reflecting the course of the unit stress (Pρdp), necessary to generate compaction equal to the dry density of solid particles obtained in the Proctor apparatus (ρdp) in relation to the sample moisture (ws). It was stated that the stress value Pρdp on the soil sample in the uniaxial compression test depends significantly on ws. It was proved that for the purpose of comparing the results of both tests, the uniaxial stress of samples must be performed in conditions of their lateral expansion. It was also proved that the use of the uniaxial test with possible lateral expansion of soil with a model sample, a diameter of which is 100 and the height is 30 mm, one may determine the obtained compaction with the use of the plate movement value.